Hemothorax following Uncomplicated Endoscopic Variceal Sclerotherapy and Ligation for Esophageal Varices - Ochiai, Tomoko (Case Rep Gastroenterol, 2017)
Endoscopic variceal sclerotherapy and ligation are standard treatment modalities used for the management of esophageal varices. Reportedly, sclerotherapy and ligation are associated with complications such as hematuria, pulmonary thrombus formation, pleural effusion, renal dysfunction, and esophageal stenosis. However, hemothorax following sclerotherapy and ligation has not yet been reported. We treated a patient who presented with liver cirrhosis and polycythemia vera and later developed hemothorax following the above-mentioned procedures. An 86-year-old man diagnosed with liver cirrhosis due to chronic hepatitis type B and alcohol abuse underwent variceal sclerotherapy using ethanolamine oleate to treat his esophageal varices. Oozing from the esophageal varices continued even after the sclerotherapy procedure; therefore, we performed endoscopic variceal ligation. The patient developed left-sided hemothorax within 24 h after treatment of his varices, and an emergency thoracotomy was performed. A pulmonary ligament of the left lung was bulging and ripping because of mediastinal hematoma, and oozing was noted. Cessation of bleeding was noted after the laceration of the left pulmonary ligament had been sutured. Ours is the first case of hemothorax reported in a patient following an uncomplicated procedure of sclerotherapy and ligation.